(2)
(6)
(-2)
--
(-3)
(+2)
(7)
(-4)
(-5)
(-2)
(-2)
(42)
(+1)
Anexos:
![](https://pt-static.z-dn.net/files/d7d/a687f84073961d800ac912504426ccab.jpg)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
Como o sinal está ( + ) vai somar
1º linha:
(-2)+(-3)=(-5)
(-2)+(+2)=0
(-2)+(-4)= (-6)
(-2)+(-5)= (-7)
2º linha
(+2)+(-3)=(-1)
(+2)+(+2)=(+2)
(+2)+(-4)= (-2)
(+2)+(-5) = (-3)
sirley62:
muito obrigado
Perguntas interessantes
Biologia,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Biologia,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás